Morphometry And Reproduction Biology Analysis Of Bullet Tuna (Auxis rochei) Landed In Kedonganan Fish Landing Base, Bali - Suryati, Yohana Deni; Setyawati, Iriani; Yusup, Deny Suhernawan (Metamorfosa: Journal of Biological Sciences, 2023)
Objective of this research is to study morphometry and reproduction biology of bullet tuna ( Auxis rochei , Risso 1810), landed in PPI ( Pangkalan Pendaratan Ikan – Fish Landing Base) Kedonganan, Bali. Morphometric aspect covers distribution of length measurement and correlation of length-weight, while gonad maturity is observed hystologically based on gonad cell growth. Result of this study shows that the length of bullet tuna ranges from 16.5 to 35.3 cmFL, with weight extends from 64.8 to 539.4 gram. Growth pattern of bullet tuna is positively allometric (b>3). Generally, landed bullet tuna in PPI Kedonganan are dominated by mature fish with Gonad Maturity Level III, IV, and V by as many as 123 individuals (58.85%) within 22 – 23 cmFL length. The difference of gonad maturity result that bullet tuna spawning season is asynchronous (multiple spawning) and partial spawning   Keywords : bullet tuna, length – weight correlation, reproduction aspect, gonad